Guest Satisfication With The Room Attendant's Performance At Hotel Inna Parapat In Handling Lost And Found Items - Rianto Manurung (Enrichment : Journal of Management, 2021)
The purpose of this research is to avoid the loss of tanu items staying at the inna parapat hotel. When working, a Room Attendant must always provide good service to guests and always dress neatly because the appearance of a Room Attendant greatly affects the guest's impression of the hotel. The presence of guests must always get more attention from the hotel, for example in the field of guest services while at the hotel such as cleanliness, neatness, and comfort and of course Room Attendant service in preparing guest needs. Because a Room Attendant is required to always be skilled and responsible in carrying out their duties. By using Observation, Questionnaire, and also Literature Study, the writer analyzes its implementation. The study was conducted at the Inna Parapat Hotel, this aims to improve the management of Inna Parapat Hotel to pay more attention to the work of their subordinates. At the time the author conducted research at Inna Parapat Hotel, the results of the research conducted by the author, the author found that the Room Attendant who worked was not in accordance with what had been set, and the lack of responsibility for lost and found items belonging to hotel guests became one of the biggest obstacles in Inna Parapat Hotel, so Room Attendant work is not optimal. This is due to the lack of supervision from supervisors to their subordinates. The author found that the Room Attendant was not working according to what had been set, and the lack of responsibility for lost and found items belonging to hotel guests was one of the biggest obstacles at Inna Parapat Hotel, so that the Room Attendant's work was not optimal. This is due to the lack of supervision from supervisors to their subordinates. The author found that the Room Attendant was not working according to what had been set, and the lack of responsibility for lost and found items belonging to hotel guests was one of the biggest obstacles at Inna Parapat Hotel, so that the Room Attendant's work was not optimal. This is due to the lack of supervision from supervisors to their subordinates.